2019
DOI: 10.1002/hpm.2804
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk associated with gambling among the youth in Rubaga Division, Kampala

Abstract: Summary The status of sexual and reproductive health of youths and adolescents in urban areas across the globe is alarming. Evidence from Uganda Aids Indicator Survey 2011 indicates that over 31% youths who have never married are engaged in sexual intercourse but have never tested for HIV. Gambling is clearly on the increase in major towns and cities drawing in several youths. However, the risk that this practice poses on the youth's sexual behavior has not been investigated in Uganda. This study intended to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…According to a study in Uganda, 62% of youth gambled, and gamblers were more male than female. The findings from the current study also found that male adolescents gamble more than female adolescents [ 45 ]. A systematic review of national studies published in 2014 reported that the prevalence of problem gambling in North America was in the range of 2.1% to 2.6%, and in Oceania from 0.2% to 4.4%.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…According to a study in Uganda, 62% of youth gambled, and gamblers were more male than female. The findings from the current study also found that male adolescents gamble more than female adolescents [ 45 ]. A systematic review of national studies published in 2014 reported that the prevalence of problem gambling in North America was in the range of 2.1% to 2.6%, and in Oceania from 0.2% to 4.4%.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, studies may differ significantly based on inclusion criteria and target populations. These methodological discrepancies have led to outcomes that vary greatly from country to country or between different studies in the same country [ 45 ]. The vast majority of adolescents who gamble consider themselves prone to problem behaviors, and they may not see a link between gambling and health risk, particularly RSB.…”
Section: Discussionmentioning
confidence: 99%
“…Also, similar issues have started to occur among neighbors to EAC countries, such as Malawi, where the odds ratios of alcohol and substance abuse, involvement in physical fights, theft, and vandalism were 4.17, 2.26, 3.26, and 3.96 times higher among gamblers, respectively [ 12 ]. In Uganda, evidence suggests that problem gambling is associated with mental health problems such as depression, anxiety, and suicidality [ 13 ]. Another study in Uganda reported 21 cases of suicide among university students, five of which were gambling-related [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies may differ signi cantly based on inclusion criteria and target populations. These methodological concerns have led to outcomes that vary greatly from country to country or between different studies in the same country [50]. The vast majority of adolescence who gamble consider themselves prone to problem behaviors, and they may not see a link between gambling and health risk, particularly RSB.…”
Section: Factors Associated With Rsbmentioning
confidence: 99%
“…However, this uncertainty makes gambling addicts prone to anger and irrational outbursts. These mood disorders also make gamblers more vulnerable to unprotected sex and sex with multiple sex partners, or even exchanging sex for cash or inkind compensation if gambling debt becomes too onerous [50].…”
Section: Factors Associated With Rsbmentioning
confidence: 99%